2022
DOI: 10.1155/2022/6034971
|View full text |Cite
|
Sign up to set email alerts
|

PFP‐LHCINCA: Pyramidal Fixed‐Size Patch‐Based Feature Extraction and Chi‐Square Iterative Neighborhood Component Analysis for Automated Fetal Sex Classification on Ultrasound Images

Abstract: Objectives. Fetal sex determination with ultrasound (US) examination is indicated in pregnancies at risk of X-linked genetic disorders or ambiguous genitalia. However, misdiagnoses often arise due to operator inexperience and technical difficulties while acquiring diagnostic images. We aimed to develop an efficient automated US-based fetal sex classification model that can facilitate efficient screening and reduce misclassification. Methods. We have developed a novel feature engineering model termed PFP-LHCINC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Further, Rueda et al aimed at investigating the fetal nutritional status using AI-assisted assessment of the adipose and fat-free tissue of the fetal arm in US images [181]. Lastly, an AI model for the automated classification of fetal sex in 2D US images of the genital area was established by Kaplan et al that helped reduce misclassification and facilitate screening [182].…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Rueda et al aimed at investigating the fetal nutritional status using AI-assisted assessment of the adipose and fat-free tissue of the fetal arm in US images [181]. Lastly, an AI model for the automated classification of fetal sex in 2D US images of the genital area was established by Kaplan et al that helped reduce misclassification and facilitate screening [182].…”
Section: Miscellaneousmentioning
confidence: 99%
“…sification of fetal sex in 2D US images of the genital area was established by Kaplan et al that helped reduce misclassification and facilitate screening [182].…”
Section: Applications In Gynecologymentioning
confidence: 99%
“…This may not apply to other types of ultrasound scans. Other studies have explored the use of ultrasound in the classification of maternal–fetal standard planes in specific clinical scenarios, such as the detection of fetal gender 24 and the estimation of fetal gestational age 25 , 26 . In summary, various research has demonstrated that ultrasound may be used to classify maternal fetal standard plans, with good results for both 2D and 3D approaches, as well as the application of AI algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Some studies focus on the identi cation of one fetal standard plan this may not apply to other types of ultrasound scans. Other studies have explored the use of ultrasound in the classi cation of maternal-fetal standard planes in speci c clinical scenarios, such as the detection of fetal gender [24] and the estimation of fetal gestational age [25] [26]. In summary, various research has demonstrated that ultrasound may be used to classify maternal fetal standard plans, with good results for both 2D and 3D approaches, as well as the application of AI algorithms.…”
Section: Related Workmentioning
confidence: 99%